Investigation of the Effects of Different Modified Asphalts on Storage Stability - Yalcin, Beyza Furtana; Yilmaz, Mehmet; Yalcin, Erkut; Ozdemir, Ahmet Münir (Avestia Publishing, 2024)
In this study, the storage stability of modified bitumen prepared with bitumen additives styrene-butadiene-styrene (SBS) and American Gilsonite (AG) was evaluated. For this purpose, modified bitumen was prepared by using different ratios of each additive type. The prepared modified bitumens were subjected to storage stability test according to EN 13399 standard. Penetration, softening point and rotational viscometry tests were performed on the samples subjected to storage stability test. As a result of the penetration and softening point tests of the samples prepared with SBS after storage stability, it was determined that the penetration and softening point values of the samples obtained from the upper part of the tube were higher. This is thought to be due to the accumulation of SBS, which has a lower specific gravity than bitumen, in the upper part of the tube during the storage stability test. Considering the viscosity test results, it was determined that the viscosity values of the modified bitumen samples obtained from the upper part of the tubes were higher than the samples obtained from the lower part of the tubes. © 2024, World Congress on Civil, Structural, and Environmental Engineering. All rights reserved.
9th World Congress on Civil, Structural, and Environmental Engineering, CSEE 2024 -- 14 April 2024 through 16 April 2024 -- London -- 312559
Keywords: American Gilsonite; Bitumen; Modification; Storage stability; Styrene-butadiene-styrene